Upaya Peningkatan Pemahaman Ibu Hamil Tentang Kepatuhan Ibu Hamil Dalam Mengkonsumsi Tablet Fe : Upaya Peningkatan Pemahaman Ibu Hamil Tentang Kepatuhan Ibu Hamil Dalam Mengkonsumsi Tablet Fe - Gladeva Yugi Antari; Ririn Supianti (Yayasan Ahmad Mansyur Nasirah, 2022)
Efforts to reduce the mortality rate of pregnant women still cannot be maximized due to the COVID-19 pandemic that has hit the world. The prevalence of anemia in pregnant women is still high both at the national level and in NTB. Complications that cause death in the mother, one of which is caused by bleeding. This bleeding can be caused by maternal conditions during pregnancy such as anemia. This anemia itself can be prevented by adherence to consuming Fe correctly. The purpose of this service is to increase the knowledge of pregnant women about anemia as a prevention of the incidence of anemia in pregnant women so that it can have an impact on reducing mortality. The method in this service is to provide counseling about anemia in pregnant women and how to consume Fe correctly, which is carried out at the Moyo Hulu Health Center with a total of 11 pregnant women participating. Based on the results of the pre-test and post-test conducted, it was found that there was an increase in knowledge and understanding of mothers about anemia and the benefits of Fe tablets. It is hoped that there will be changes in the behavior of pregnant women in caring for their pregnancy so that pregnancy complications such as anemia can be prevented by consuming Fe properly.